Frequency Distribution The size of the dominant fish caught in Trap Net fishing gear in coastal waters, Sigeri District, Pangkep Regency - Ihsan, Ihsan; Jamal, Muhammad; Asbar, Asbar; Sadaria, Sadaria (Agrikan Jurnal Agribisnis Perikanan, 2021)
Coastal fishing ground (coastal fishing ground) has abundant resources, this is due to the fertile waters environment where the coral reefs, seagrass and mangrove ecosystems are still quite good. The purpose of the study was to determine the frequency distribution of the size of the dominant trap net fishing gear caught in the coastal waters of Sigeri District, Pangkep Regency. The object of this research is fish caught by trap net. The data collected consists of primary and secondary data. The equipment used is a fish measuring ruler, digital scales, office stationery, global position system. data were analyzed descriptively qualitatively and quantitatively. The results of the study, the frequency distribution of the size of the dominant trap net fishing gear caught in the coastal waters of Sigeri District, Pangkep Regency, which consisted of lompa fish (Trissina baelama), mullet (Mugil Sp), kurau (Polydactylus octonemus), titang (Scatophagus sp), rejung (Sillago sihama), cotton (Geres punctatus), gulamah (Johnius trachycephalus), and white shrimp (Litopenaeus vannamei). Most of the fish caught are in the category of small fish and a small proportion are included in the size of adult fish, and all fish caught are economically important fish.